2018
DOI: 10.1063/1.5064757
|View full text |Cite
|
Sign up to set email alerts
|

Inflection point in the Debye relaxation time of 2-butyl-1-octanol

Abstract: We report a striking anomaly in the pressure dependent Debye-relaxation time of the branched monohydroxy alcohol 2-butyl-1-octanol. Evidence of a crossover from slower to faster than exponential pressure dependency was obtained at different temperatures via high pressure broadband dielectric spectroscopy. At the same time, viscosity measurements reveal similar behavior in the viscosity respectively the structural relaxation time, indicating a similar origin of the phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Dielectric relaxation study of the dynamics of monohydroxyl alcohols is not only historic since the work of Debye but also it continues to be an active research topic till the present time. The slowest Debye process in the dielectric spectra of many monohydroxyl alcohols commands attention because of its exceptionally high intensity and extremely narrow frequency dispersion or exponential time-dependent relaxation function. The more recent efforts including nuclear magnetic resonance, dielectric relaxation at elevated pressures, ,, shear mechanical relaxation, and neutron scattering measurements have shown that the Debye relaxation originates from the dynamics of transient supramolecular or short-chain structures , of these hydrogen-bonded liquids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dielectric relaxation study of the dynamics of monohydroxyl alcohols is not only historic since the work of Debye but also it continues to be an active research topic till the present time. The slowest Debye process in the dielectric spectra of many monohydroxyl alcohols commands attention because of its exceptionally high intensity and extremely narrow frequency dispersion or exponential time-dependent relaxation function. The more recent efforts including nuclear magnetic resonance, dielectric relaxation at elevated pressures, ,, shear mechanical relaxation, and neutron scattering measurements have shown that the Debye relaxation originates from the dynamics of transient supramolecular or short-chain structures , of these hydrogen-bonded liquids.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not an easy task because the slower Debye process makes it difficult to resolve the α-relaxation and determine its frequency dispersion, even after the contribution of the former to the spectrum has been subtracted off. , Located at higher frequencies, the β-relaxation usually has weak relaxation strength and not resolved in the liquid and rarely shown in the glassy state. The situation is improved by the most recent experimental studies of two monohydroxyl alcohols, 1-propanol and 5-methyl-2-hexanol (5M2H), by very broadband dielectric spectroscopy (with additional time domain dielectric experiments) and depolarized dynamic light scattering (DDLS). The α-relaxation and the β-relaxation appear in the DDLS spectra in good agreement in the dynamics with that observed in the dielectric spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, over the years, only a limited number of glass-forming materials have been proven to reveal inflection points experimentally—that is, glycerol, propylene carbonate (PC), Error! Bookmark not defined , 52 2-butyl-1-octanol, 30 protic IL [C 8 HIm][NTf 2 ], 53 and recently [P 666,14 ][BOB]. 54 Casalini and Bair suggested that the origin of the inflection point in PC can be attributed to the pressure dependences of compressibility and the apparent activation energy at a constant volume.…”
Section: Resultsmentioning
confidence: 99%
“…A significant advantage of the BDS technique is the possibility of studying the dynamics of ions and, thus, their nanoordering at elevated pressure . It has been many times demonstrated that the dc-conductivity (σ dc ), quantifying the ion dynamics of protic, aprotic, and polymerized ILs, can be determined with very high precision at various T – P thermodynamic conditions, not only in the equilibrium liquid state but also near the liquid–glass transition. , This gives a unique opportunity to investigate the effect of the pressure on the self-assembly of ILs.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of the Debye relaxation have been extensively performed in supercooled liquids using various strategies such as elevating pressure, confinements and mixing [23][24][25][26], and new recognition and understanding is greatly enhanced [27][28][29][30][31]. In earlier dielectric studies of two typical monoalcohols, one being primary 2-ethyl-1-hexanol (2E1H) and the other secondary 4-methyl-3-heptanol (4M3H), it is found that the two key ratios of the relaxation strength and relaxation time between the Debye and structural dynamics at high pressure, Δε D /Δε α and τ D /τ α are correlated inversely [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%